A design method for supporting the development and integration of ARTful global schedulers into multiple programming models - Santana, Alexandre de Limas (2019)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2019.